If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 9 = 9x + 7 Reorder the terms: 9 + 7x = 9x + 7 Reorder the terms: 9 + 7x = 7 + 9x Solving 9 + 7x = 7 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 9 + 7x + -9x = 7 + 9x + -9x Combine like terms: 7x + -9x = -2x 9 + -2x = 7 + 9x + -9x Combine like terms: 9x + -9x = 0 9 + -2x = 7 + 0 9 + -2x = 7 Add '-9' to each side of the equation. 9 + -9 + -2x = 7 + -9 Combine like terms: 9 + -9 = 0 0 + -2x = 7 + -9 -2x = 7 + -9 Combine like terms: 7 + -9 = -2 -2x = -2 Divide each side by '-2'. x = 1 Simplifying x = 1
| b=8m+9 | | 8x=26+14y | | 18-2x+x=6x-3 | | 90+45w=960 | | -132+2x=-6x+44 | | (x+2)-4=-3x+12 | | 4w+7x-13y+5w+5x+7y= | | 4y-2(4)=16 | | 42=14y-7y | | -132+2x=10x+50 | | 5+x+3x=4x+5 | | (2x^2+11x-18)=0 | | -6x-78=57-x | | 10=6y+2+3y+17 | | 4+3+2+6+10= | | 4(x-1)=5.6 | | 2(m-22)+3(m-4)=36 | | 1.4(5x-0.2)= | | x+-39=-2x+33 | | 25(2x^2+11x-18)=0 | | z-39=-2x+33 | | 40-5w=3w | | 2e-5=-4.6 | | 5x+(-x)= | | 3n-7n+12=32 | | 6z=16 | | 19.8x=91 | | 50x^2+275x-450=0 | | -51+6x=84+11x | | 9(s+3)-34= | | 4x-6x+x-9x= | | -2a+-9=6a+13 |